REPRESENTATION OF BALINESE CULTURE IN GUN GUN’S MAHABHARATA EPIC PUPPET COMIC - I Wayan Nuriarta; I Nyoman Darma Putra; I Nyoman Suarka; Ida Ayu Laksmita Sari (E-Journal of Cultural Studies, 2024)
The Mahabharata epic is better known to people in Bali, especially in shadow puppet plays. However, since 1955, the Mahabharata epic has been presented in the form of comics. This way of storytelling continued until 2014 with the printing of the Mahabharata epic puppet comic by Gun Gun, which presents Balinese cultural icons. This research aims to describe the representation of Balinese culture in Gun Gun’s Mahabharata epic puppet comic. The research method employed a critical qualitative design. Data collection was conducted through observation, interview, and literature study. The theories utilised are comic theory, hegemony theory, representation theory, and articulation theory. The findings indicate that Gun Gun’s Mahabharata epic puppet comic employs three forms of Balinese cultural representation. The three forms are as follows: (1) visual representation, whereby characters and backgrounds are depicted in comics in a manner that evokes Balinese architecture, including wantilan, pura, and togog; (2) verbal representation, which is evidenced by the presence of Balinese vocabulary in the dialogue of the characters, such as om swastiastu, kerahayuan, yadnya, Hyang Widhi, and darma; and (3) narrative representation, which is evident in the explicit portrayal of Hindu teachings, including karma phala. The dialogue of the characters, such as om swastiastu, kerahayuan, yadnya, Hyang Widhi, and darma, and the narrative representation that shows explicitly the teachings of Hinduism, such as karma phala, are also forms of cultural representation. The study of Balinese cultural representation in the Mahabharata epic comic contributes to the understanding that comics also serve as a medium for the adaptation of external cultural influences, thereby reinforcing Balinese identity. Keywords: Balinese culture, Mahabharata epic, comics, representation, Balinese identity